The Impact of BCR-ABL1 Transcript Type on Tyrosine Kinase Inhibitor Responses and Outcomes in Patients with Chronic Myeloid Leukemia - (:unkn) unknown (WILEY, 2018)
Although the majority of patients with chronic myeloid leukemia do well with treatment with tyrosine kinase inhibitors (TKIs), some patients still have inferior outcomes. There are many factors that might play a part, including the different BCR-ABL1 transcript types at baseline. The current study was performed to determine the possible impact of different transcripts on the treatment responses and outcomes of patients with chronic myeloid leukemia who are receiving TKI therapy. The authors performed a systematic literature search by using the terms b2a2/b3a2, e13a2/e14a2, or transcript type. e14a2 was the more common transcript type. The majority of the studies demonstrated no significant difference regarding age, sex, leukocyte counts, and hemoglobin levels between patients with the e13a2 and e14a2 transcripts. However, in approximately one-half of the studies, the e14a2 transcript was associated with higher platelet counts. Almost no studies demonstrated a significant association between disease risk scores and transcript types. In the majority of studies, having the e14a2 transcript was associated with earlier, deeper, and higher molecular response rates. Although better event-free survival was observed in patients with the e14a2 transcript in some of the studies, the majority demonstrated that transcript type did not have an impact on progression-free and overall survival. Treatment-free remission currently is a topic of much interest, and to the authors' knowledge there are limited data with conflicting results regarding the possible effects of transcript types on the outcomes of patients after discontinuation of TKIs. Because having the e14a2 transcript appears to be related to a favorable outcome, choosing second-generation TKIs for frontline therapy might be a convenient approach in patients with chronic myeloid leukemia with the e13a2 transcript. The authors believe this finding warrants further investigation.
Keywords: BCR-ABL1; chronic myeloid leukemia (CML); e13a2; e14a2; response; transcript; tyrosine kinase inhibitor (TKI); CHRONIC MYELOGENOUS LEUKEMIA; MINIMAL RESIDUAL DISEASE; TREATMENT-FREE REMISSION; ABL FUSION TRANSCRIPTS; LONG-TERM SURVIVAL; CHRONIC-PHASE; CYTOGENETIC RESPONSE; MOLECULAR RESPONSE; IMATINIB TREATMENT; IRANIAN PATIENTS